A Digest of the Laws and Ordinances for the Government of the Municipal Corporation of the City of Reading 240 (1897) - (:unkn) unknown (My University, 1897)
City Park, § 20(8) : Prohibited any person from carrying firearms, or discharge in the common or within fifty yards therof, or throw stones or other missiles therein.
Keywords: CARRY - CERTAIN PUBLIC PLACES; DISCHARGE